2012
DOI: 10.1016/j.jalz.2011.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Citalopram for agitation in Alzheimer's disease: Design and methods

Abstract: Background Agitation is one of the most common neuropsychiatric symptoms of Alzheimer’s disease (AD), and is associated with serious adverse consequences for patients and caregivers. Evidence-supported treatment options for agitation are limited. The citalopram for agitation in Alzheimer’s disease (CitAD) study was designed to evaluate the potential of citalopram to ameliorate these symptoms. Methods CitAD is a randomized, double-masked, placebo-controlled multicenter clinical trial with two parallel treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 58 publications
0
56
0
Order By: Relevance
“…CitAD participants had probable Alzheimer's disease as defined by NINCDS-ADRDA [17] criteria, Mini-Mental State Examination (MMSE) [18] scores of 5-28 inclusive, and clinically significant agitation. The detailed list of eligibility criteria for CitAD has been published previously [19]. The protocol for CitAD and supporting CON-SORT checklist are available as supporting information; see Protocol S1 and Checklist S1.…”
Section: Citad Designmentioning
confidence: 99%
See 1 more Smart Citation
“…CitAD participants had probable Alzheimer's disease as defined by NINCDS-ADRDA [17] criteria, Mini-Mental State Examination (MMSE) [18] scores of 5-28 inclusive, and clinically significant agitation. The detailed list of eligibility criteria for CitAD has been published previously [19]. The protocol for CitAD and supporting CON-SORT checklist are available as supporting information; see Protocol S1 and Checklist S1.…”
Section: Citad Designmentioning
confidence: 99%
“…The CitAD sample size requirements were based on the primary outcomes and have been published [19,20]. Enrollments following the introduction of the new ECG monitoring procedures in 2011 continued to be balanced between the citalopram and placebo groups.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Patients with depressive or psychotic symptoms requiring treatment were excluded. The CitAD study also measured safety and tolerability of the active treatment as well as its effect on caregiver distress [14]. The study found statistically significant and clinically meaningful reduction in agitation in the citalopram group over placebo on both primary outcome measures: The Neurobehavioral Rating Scale, agitation subscale estimated treatment difference at week 9 (citalopram minus placebo) was -0.93 points (95% CI: -1.80 to -0.06; p = 0.04).…”
Section: Citaloprammentioning
confidence: 99%
“…For decades, antipsychotics have been the pragmatic mainstay of treatment despite their limited efficacy, and history of adverse events outweighing potential benefits including FDA black box warnings [13]. Risks surrounding antipsychotic use, both conventional and atypical, range from weight gain, falls and drowsiness to increased cerebrovascular events and mortality rate in elderly individuals [14]. Major efforts are underway in the USA and worldwide to limit the use of antipsychotics in patients with dementia due to these safety concerns.…”
mentioning
confidence: 99%
“…ADMET will also use a clinician rating of target behavior change similar to the approach used in the Depression in Alzheimer’s Disease Study-2 (DIADS-2) (26) and the Citalopram for Agitation in Alzheimer’s Disease (CitAD) trial (27). We modified the ADCS-CGIC by adding apathy-specific interview questions and probes based on Marin’s core features of apathy: lack of initiative, lack of interest and emotional blunting (16).…”
Section: Issues In Designing a Trial To Test Treatments For Apathymentioning
confidence: 99%